Swedish election study 2002 - Holmberg, Sören; Ekengren Oscarsson, Henrik; Statistics Sweden (University of Gothenburg, 2004)
This is the fifteenth election study carried out in Sweden in connection with a Swedish general election. Many of the questions are replications of questions asked in one or several of the previous surveys, but there are also a number of questions not asked before.

The interview included questions on how much the respondent takes part of political matters in mass media; political interest in general and political discussions among family and friends; important issues when deciding how to vote; and preferred formation of the government after the election and person preferred as prime minister, as well as opinion on government and opposition 1998-2002 and assumptions how the Social Democrats and the bourgeois parties respectively would manage as governing party/parties 2002-2006. There were also a number of questions on the opinions of the political parties regarding: employment, the Swedish economy, taxes, the conditions for enterprise, environment, energy and nuclear power, social security, care of the elderly, health and medical service, child care, school and education, ethics and moral, law and order, equality, sparsely-populated areas, foreign affairs and security policy, aid to developing countries, the European Union, EMU, refugees and immigration, US war on terrorism, Middle East conflict, and NATO. Political parties and party leaders were to be placed on a scale ranging from strongly dislike to strongly like. Respondents also had to give their opinion on the Social democratic party and the Conservative party and their party leaders with regard to how reliable, inspiring, and sympathetic they are and how much they know about what ordinary people likes. The respondents also had to state how much confidence they had in Swedish politicians. The respondent had to rate a great number of suggestions occuring in the political debate. A number of questions dealt with party preference; vote in the September elections; things important when choosing party; votes in earlier elections. As in earlier election studies the respondent had to place the political parties on a political left-right scale. In this survey the political parties also had to be placed on a scale concerning their opinion towards EMU. The respondent also had to place herself/himself on these scales.

Purpose:

Explain why people vote as they do and why an election ends in a particular way. Track and follow trends in the Swedish electoral democracy and make comparisons with other countries.

Detta är den femtonde riksomfattande studien i serien undersökningar kring partival, valdeltagande och opinionsbildning inom den svenska valmanskåren i samband med ett riksdagsval. Undersökningen ingår som steg två i panelen 1998-2002 och som steg ett i panelen 2002-2006. Ett stort antal av frågorna har ställts i en eller flera tidigare valundersökningar.

Syfte:

Förklara varför väljare röstar som de gör och varför val slutar som de gör. Spåra och följa trender i svensk valdemokrati och göra jämförelser med utvecklingen i andra länder.
Svensk valundersökning 2002
VU02
Keywords: elections; val; participation; deltagande; politics; politik; voting intention; röstavsikt; voting; röstning; parliamentary elections; riksdagsval; political interest; politiskt intresse; political behaviour; politiskt beteende; nato; nato; party identification; partiidentifikation; information materials; informationsmaterial; election broadcasting; valbevakning i tv och radio; languages; språk; news; nyheter; privatization; privatisering; political allegiance; politisk anhängare; political participation; politiskt deltagande; government; regering; information retrieval; informationssökning; internal politics; inrikespolitik; political parties; politiska partier; european economic and monetary union; europeiska ekonomiska och monetära unionen; political leaders; politiska ledare; election campaigns; valkampanjer; electoral issues; valfrågor; opposition parties; oppositionspartier; political attitudes; politiska åsikter; political issues; politiska frågor; CORS; CORS; Media; Media; Political behaviour and attitudes; Politiska beteenden och attityder; Elections; Val; Government, political systems and organisations; Regering, politiska system och organisationer; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap